Particles Ka(h) of Indonesian and Japanese: Cross Linguistic Study - Maharani Patria Ratna (Universitas Diponegoro, 2020)
Some languages in the world have particles with their respective functions. One of them is Ka(h) particle which is used both in Indonesian and Japanese. Both are equally used as markers of the question sentence. In Indonesian the ka(h) particle is pronounced